Evaluation of the individual radiosensitivity of a person on the basis of differentiated coloring of chromosomes in peripheral blood lymphocytes - Domina, E.A.; Gontar, J.V.; Illyuchok, L.A.; Grynchenko О.O. (Reports of the National Academy of Sciences of Ukraine, 2019)
A determination and a prediction of the individual radiation sensitivity (IRS) of a person remains an actual problem in the field of radiobiology. The chromosomal aberrations of a stable type, which are recognized as radiation in dicators, may be involved in the malignant cell transformation. Under the classical cytogenetic analysis (a uniform staining of cells), stable aberrations appear only in 20 % of cases. The use of differential cell coloration makes it possible to identify the most complete spectrum of radiation-induced chromosome aberrations, including stable types, which act as the threat of an increased carcinogenic risk. The aim is to determine the frequency and spectrum of radiation-induced chromosome aberrations in blood lymphocytes of persons with a high IRS. A cytogenetic examination of persons with a high individual radiosensitivity (coefficientirs 1.2—1.7) was carried out on the basis of the differentiated coloring of chromosomal preparations in blood lymphocytes. A high individual radiosensitivity to a radiation is combined with the stable-type aberrations of chromosomes 3, 5, 9, and 14. This indicates an increased risk of developing a cancer. It has also been shown that the chromosomes participate in the rearrangements with different frequencies, which indicates their interindividual sensitivity to radiation. Within the framework of the performed cytogenetic study, the highest sensitivity to the irradiation was found in chromosome 5. Chromosome Y was not involved in the formation of the rearrangements. The introduction of the developed “Passport of individual radiosensitivity of a person according to the cytogenetic parameters” is recommended in order to improve the quality of the clinical examination of professionals working in the field of ionizing radiation.